Cost-effectiveness of HIV pre-exposure prophylaxis among female sex workers in Iran - Hossein Moameri; Reza Goudarzi; Ali Akbar Haghdoost; Mohammad Mehdi Gouya; Parya Saberi; Ali Mirzazadeh; Parvin Mangolian Shahrbabaki; Hamid Sharifi (Scientific Reports)
Abstract The Iranian government does not fund pre-exposure prophylaxis (PrEP), and it is not used in Iran due to uncertainties in its cost-effectiveness. In this study, we examined the cost-effectiveness of PrEP among female sex workers (FSWs) in Iran. The cost-effectiveness analysis compared only PrEP, a combination of PrEP with harm reduction (HR) with only HR scenario among FSWs over a 10-year time horizon. The perspective of the healthcare provider was used in the analysis. The primary outcome was disability-adjusted life year (DALY) averted. Analyses included health and cost outcomes, as well as the incremental cost-effectiveness ratio (ICER), which was reported as the cost per DALY averted. Only PrEP was not cost-effective at a willingness to pay threshold of 4669.6 USD per DALY averted in Iran. In contrast, PrEP and HR strategies were cost-effective at the same willingness to pay threshold. The ICER was 868.47 USD per DALY averted for PrEP and HR compared to HR alone. Compared to HR, combining PrEP with HR is a cost-effective intervention among Iranian FSWs for reducing the clinical and economic burden associated with HIV over a 10-year time horizon. Iran should add PrEP to current HR programs for FSWs.